The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.joa.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the wearable cardioverter defibrillator in patients in the early post‐myocardial infarction phase with high risk of sudden cardiac death: A single‐center European experience

Abstract: Early post-MI patients at high risk of sudden cardiac death may benefit from WCD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…After title/abstract screening and full-text assessment, 11 studies with nonoverlapping populations and/or endpoints evaluating a cumulative total of 19,882 patients (range: 8-8,453 patients) were included (Table 2). 5,6,[11][12][13][14][15][16][17][18][19] Most studies were retrospective (n = 9; 82%) and multicenter (n = 7; 64%) in nature, with five studies (45%) incorporating data from the manufacturer's registry. Of the studies considered, 56% evaluated patients treated in the US (n = 6), while 36% evaluated patients treated in Germany (n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…After title/abstract screening and full-text assessment, 11 studies with nonoverlapping populations and/or endpoints evaluating a cumulative total of 19,882 patients (range: 8-8,453 patients) were included (Table 2). 5,6,[11][12][13][14][15][16][17][18][19] Most studies were retrospective (n = 9; 82%) and multicenter (n = 7; 64%) in nature, with five studies (45%) incorporating data from the manufacturer's registry. Of the studies considered, 56% evaluated patients treated in the US (n = 6), while 36% evaluated patients treated in Germany (n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…After addition of two citations identified by hand search, forty-six primary studies, two systematic reviews, and one HTA were included for final analysis (see Figure 1). The forty-six primary studies included one RCT 7, one nrCT (11), sixteen non-comparative prospective trials (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and twenty-eight non-comparative retrospective trials (4;28-54). The RCT showed a low and the nrCT a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…According to our selection criteria, no randomized controlled trials (RCTs) or non-randomized controlled trials assessing the clinical effectiveness of the WCD were found. For the assessment of safety, one prospective interventional single-arm study, 20 two prospective case series, 21 , 22 and two prospective registry studies 23 , 24 fulfilled our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A total of five non-comparative studies were included in the assessment of safety of the WCD: the prospective interventional single-arm study 20 included 289 patients, two prospective case series included a total of 36 patients, 21 , 22 and two prospective registry studies included a total of 2089 patients 23 , 24 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%